1988
DOI: 10.1101/gad.2.7.786
|View full text |Cite|
|
Sign up to set email alerts
|

Isolation of a recombinant copy of the gene encoding C/EBP.

Abstract: In two previous studies we described the properties of a heat-stable DNA-binding protein present in rat liver nuclei. This protein, hereafter termed C/EBP, is capable of selective binding to the CCAAT homology of several viral promoters (Graves et al. 1986), as well as the core homology common to many viral enhancers (Johnson et al. 1987). We now report the isolation of a recombinant clone of the gene that encodes C/EBP. Expression of the clone in bacterial cells yields a protein that binds in vitro to both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
610
0
3

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 960 publications
(622 citation statements)
references
References 54 publications
9
610
0
3
Order By: Relevance
“…Kuo et al {1991) have demonstrated that the two chains are subject to different regulatory influences during F9 differentiation, a result that is consistent with our finding that the two chains are expressed at widely varying levels in different tissues. Although several transcription factors have been described that are selectively expressed in the liver, including C/EBP {Johnson et al 1987;Landschulz et al 1988a), DBP (Mueller et al 1990), LAP (Descombes et al 1990), HNF-3 (Lai et al 1990), andHNF-4 (Sladek et al 1991), none are entirely liver specific and none have the potential, such as MyoD or myogenin (Lassar et al 1986), to convert another cell type into a hepatocyte. Furthermore, most of these factors are expressed at the time of birth, too late in development to play a primary role in organogenesis.…”
Section: Developmental Implications Of Hnf-1 Heterodim Eriza Tionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kuo et al {1991) have demonstrated that the two chains are subject to different regulatory influences during F9 differentiation, a result that is consistent with our finding that the two chains are expressed at widely varying levels in different tissues. Although several transcription factors have been described that are selectively expressed in the liver, including C/EBP {Johnson et al 1987;Landschulz et al 1988a), DBP (Mueller et al 1990), LAP (Descombes et al 1990), HNF-3 (Lai et al 1990), andHNF-4 (Sladek et al 1991), none are entirely liver specific and none have the potential, such as MyoD or myogenin (Lassar et al 1986), to convert another cell type into a hepatocyte. Furthermore, most of these factors are expressed at the time of birth, too late in development to play a primary role in organogenesis.…”
Section: Developmental Implications Of Hnf-1 Heterodim Eriza Tionmentioning
confidence: 99%
“…The earliest example to be discovered in vertebrates was the leucine zipper family (Landschulz et al 1988b) including C/EBP, DBP, Fos, Jun, and others (Chiu et al 1988;Landschulz et al 1988a;Rauscher et al 1988;Turner and Tjian et al 1989;Mueller et al 1990). Somewhat later the helix-loop-helix group including El2, E47, myoD, and Id were found to form weak but functionally important heterodimers (Tapscott et al 1988;Murre et al 1989;Benezra et al 1990).…”
mentioning
confidence: 99%
“…All of these distinct interactions result in the differential transcriptional activity of the C/EBP isoforms. At present, six members (C/EBP ·, -ß, -Á, -‰, -Â, and -˙) with different tissue-specific expression patterns have been characterized (3,(6)(7)(8)(9)(10)(11)(12)(13)(14). C/EBPs exert pleiotropic effects based on tissue-and stage-specific gene expression, alternative translation of various protein isoforms, interaction with other transcription factors, and variable DNA-binding specificities.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the high abundance of H3K27Ac marks in this region of Gria4 suggests it is highly regulated. One possible candidate is the CCAAT/enhancer binding proteins (C/EBPs), which have a well described ability to bind CCAAT boxes (Landschulz, Johnson, Adashi, Graves, & McKnight, 1988). Irrespective of these possibilities, the knockdown, qPCR and ChIP experiments presented in this paper highlight NF‐Yb as an effective regulator of Gria 4 transcription.…”
Section: Discussionmentioning
confidence: 99%